Nutrition Intake as a Fasting Plasma Glucose Regulation Control in DMT2 Patients - Nindya Kirana, D (KnE Life Sciences, 2019)
The prevalence of type-2 diabetes mellitus (DMT2) tends to increase worldwide. The prediction numbers of diabetes mellitus (DM) patients in Indonesia will be increasing from 8.4 million people in the year of 2000 to around 21.3 million in the year of 2030. Diabetes mellitus is a syndrome with metabolism disordered of carbohydrates, fats and proteins caused by the reduced of insulin secretion or the decreased of tissue sensitivity to insulin, as the result, the blood glucose level is increased (hyperglycemia). The purpose of the study was to examine nutritional status (intake of KH, protein, fat and fiber) of type-2 DM patients. This type of research was quantitative research with cross sectional approach. The independent variable of this study is the intake of nutrients (carbohydrates, proteins, fats and fiber) to the level of fasting plasma glucose. The population of this study were 450 people of all Type 2 DM patients who were treated and controlled in Arifin Achmad Hospital, Riau Province, and the sample taken by accidental sampling as many as 37 respondents. The results of the study performed by Chi Square test showed that nutritional intake that affected fasting glucose significantly was carbohydrate (0.031), fat (0.002) and protein (0.002) while fiber did not show significant results (0.068). The results of this study will be used for further research, to create a program to overcome the increasing in fasting plasma glucose by managing the nutritional intake of Type 2 DM patients. Keywords: carbohydrate, fat, protein, as well as glucose, diabetes